Experimental and Natural Induction of de novo Centriole Formation - Takumi, Kasuga; Kitagawa, Daiju (Frontiers in Cell and Developmental Biology, 2022)
In cycling cells, new centrioles are assembled in the vicinity of pre-existing centrioles. Although this canonical centriole duplication is a tightly regulated process in animal cells, centrioles can also form in the absence of pre-existing centrioles; this process is termed de novo centriole formation. De novo centriole formation is triggered by the removal of all pre-existing centrioles in the cell in various manners. Moreover, overexpression of polo-like kinase 4 (Plk4), a master regulatory kinase for centriole biogenesis, can induce de novo centriole formation in some cell types. Under these conditions, structurally and functionally normal centrioles can be formed de novo. While de novo centriole formation is normally suppressed in cells with intact centrioles, depletion of certain suppressor proteins leads to the ectopic formation of centriole-related protein aggregates in the cytoplasm. It has been shown that de novo centriole formation also occurs naturally in some species. For instance, during the multiciliogenesis of vertebrate epithelial cells, massive de novo centriole amplification occurs to form numerous motile cilia. In this review, we summarize the previous findings on de novo centriole formation, particularly under experimental conditions, and discuss its regulatory mechanisms.